The Imposter Phenomenon Among Emerging Adults Transitioning Into Professional Life: Developing a Grounded Theory. Issue 2 (October 2015) - Lane, Joel A.
<x xml:space="preserve">Abstract</x> This study qualitatively explored the imposter phenomenon (IP) among 29 emerging adults who were transitioning into professional life. A grounded theory was developed that described IP, internal and external contributing factors, and IP's effect in terms of performance and affective reactions. Implications for counselors of emerging adults are discussed.